The Evaporation Mechanism in the Wick of Copper Heat Pipes - Wong, Shwin-Chung.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book discusses the evaporation mechanism in the wick of copper heat pipes. The investigations are based on recent visualization experiments for operating horizontal flat-plate heat pipes.
Introduction -- Experimental methods -- Water in mesh and powder wicks -- Different working fluids in 100+200 mesh wick -- Effects of surface wettability -- Conclusions.
Keywords: Fluid mechanics; Fluids; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Engineering Thermodynamics, Heat and Mass Transfer